Indigenous mental healthcare and human rights abuses in Nigeria: The role of cultural syntonicity and stigmatization - Ogunwale, Adegboyega; Fadipe, Babatunde; Bifarin, Oladayo (Frontiers in Public Health, 2023)
Background: Indigenous mental healthcare using traditional non-western methods termed “unorthodox approaches” has been observed in Nigeria historically. This has been largely due to a cultural preference for spiritual or mystical rather than biomedical formulations of mental disorder. Yet, there have been recent concerns about human rights abuses within such treatment settings as well as their tendency to perpetuate stigmatisation. Aim: The aim of this review was to examine the cultural framework for indigenous mental healthcare in Nigeria, the role of stigmatisation in its utilisation and interrogate the issues of human rights abuses within a public mental health context. Methods: This is a non-systematic narrative review of published literature on mental disorders, mental health service utilisation, cultural issues, stigma, and indigenous mental healthcare. Media and advocacy reports related to human rights abuses in indigenous mental health treatment settings were also examined. International conventions on human rights and torture, national criminal legislation, constitutional provisions on fundamental rights and medical ethics guidelines relevant to patient care within the country were examined in order to highlight provisions regarding human rights abuses within the context of care. Results: Indigenous mental healthcare in Nigeria is culturally syntonic, has a complex interaction with stigmatisation and is associated with incidents of human rights abuses especially torture of different variants. Three systemic responses to indigenous mental healthcare in Nigeria include: orthodox dichotomisation, interactive dimensionalisation, and collaborative shared care. Conclusions: Indigenous mental healthcare is endemic in Nigeria. Orthodox dichotomisation is unlikely to produce a meaningful care response. Interactive dimensionalisation provides a realistic psychosocial explanation for the utilisation of indigenous mental healthcare. Collaborative shared care involving measured collaboration between orthodox mental health practitioners and indigenous mental health systems offers an effective as well as cost-effective intervention strategy. It reduces harmful effects of indigenous mental healthcare including human rights abuses and offers patients a culturally appropriate response to their problems.